Riesgo de Artritis Reumatoidea en pobladores adultos de ambos sexos del sector Buenos Aires del distrito Víctor Larco Herrera - Alfaro Verde, Lizet Janet (2018)
This report presents the results obtained from the determination of the risk of rheumatoid arthritis through modifiable and non-modifiable factors in adult inhabitants of both sexes of the Buenos Aires sector of the Víctor Larco Herrera district. Among the modifiable factors were taken into account the body mass index (BMI), physical activity, tobacco and alcohol consumption; and non-modifiable factors such as sex, age and rheumatoid factor. The determination of the rheumatoid factor was performed with the Latex Agglutination - Polystyrene method. 40% of the samples processed were positive cases of rheumatoid factor and 60% negative cases. Regarding sex, 6% were positive cases of rheumatoid factor belonging to the male sex and 34% to the female sex. On the other hand, the distribution by age range is shown, observing a higher percentage of positive cases (12%) between 66 and 75 years. According to the BMI, 18% of positive cases present obesity, while 16% of positive cases do not perform exercises. The 56% of negative cases corresponds to the population that do not consume tobacco, 38% of negative cases belong to the population that do not consume alcohol. By means of the Chi square test (1-α = 95%, α = 0.05, k = 2gl) it was determined that there is no significant relationship with the risk factors of rheumatoid arthritis. The alternative hypothesis is rejected